(untitled) - Darmawikarta, Djoni (Toronto, 2007)
Data warehousing with MySQL, a free and popular database, has never been made easier with this step-by-step tutorial on building dimensional data warehouses. Topics include star-schema modeling, populating (Extract, Transform, and Load: ETL), testing, and dimensional querying. It comes complete with a hands-on case—scaled-down from a real project—as well as an electronic copy of all MySQL scripts and sample data available for download. Computer programmers who need to build a data warehouse will find relevant examples and information written in a thorough, easy-to-follow style.
Keywords: Kho dữ liệu,Data warehousing